PELATIHAN IMPLEMENTASI PROGRAMMING WEB MENGGUNAKAN BOOTSTRAP PADA SMK TELADAN PEMATANG SIANTAR - Abdi Rahim Damanik; Widodo Saputra; Dedy Hartama; Indra Gunawan; Surya Darma; Fahmi Firzada (Jurnal Abdimas Bina Bangsa, 2022)
Mastery of Information and Communication Technology needs to be taught at all levels so that processes and activities can be carried out more quickly, easily and efficiently. Class XI students of SMK Teladan Pematang Siantar are required to have competencies that can be mastered before leaving school in the field of website programming. One of the competencies is being able to create websites or web-based applications using CSS and bootstrap. The purpose of this Community Service Activity is to provide training in developing mastery of website programming as interactive learning for Teachers of Exemplary SMK Pematang Siantar. The devotional method used includes lectures, question and answer, discussion and practice. The steps for the Community Service program are 1) Compiling and developing training materials, 2) Training Stage, 3) The practical assistance stage in the process of making website programming implementations using css and bootstrap. Community Service shows that the training that has been carried out on activities can improve students' abilities to develop knowledge in the process of implementing website programming using bootstrap